World Bank Research Digest, Vol. 7(3) - World Bank (Washington, DC, 2014)
In this issue: have capital markets aided growth in China and India? Land and poverty: the importance of transparency; coping with $100 oil; how fit are feed-in tariff policies? Political incentives to underinvest in pro-poor policies; mass media and public policy for agriculture; and managing public debt in small states.